2019
DOI: 10.1111/vox.12826
|View full text |Cite
|
Sign up to set email alerts
|

Changing the deferral for men who have sex with men – an improved model to estimate HIV residual risk

Abstract: Background and Objectives Eight published studies modelled the impact of changing from a lifetime to time‐limited deferral for men who have sex with men (MSM); each predicted greater risk impact than has been observed. This study uses these previous efforts to develop an ‘optimized’ model to inform future changes to MSM deferrals. Materials and Methods HIV residual risk was calculated using observed HIV incidence/prevalence prior to the change in MSM deferral, then with the additional MSM expected under a 12‐m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 27 publications
(43 reference statements)
0
28
0
Order By: Relevance
“…Our model was based on the English model with the added feature of simulation to take into account the uncertainty and variability of parameters to estimate residual risk and 95% confidence intervals. Using this optimized model, we previously reported that the 12‐month deferral expected residual risk was not significantly different from the observed English and Canadian post‐implementation residual risk . The model assumes release errors will be negligible, thus does not estimate risk under conditions of emergency manual product release.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Our model was based on the English model with the added feature of simulation to take into account the uncertainty and variability of parameters to estimate residual risk and 95% confidence intervals. Using this optimized model, we previously reported that the 12‐month deferral expected residual risk was not significantly different from the observed English and Canadian post‐implementation residual risk . The model assumes release errors will be negligible, thus does not estimate risk under conditions of emergency manual product release.…”
Section: Discussionmentioning
confidence: 94%
“…We have recently published a mathematical model that combined a published English deterministic model with stochastic Monte Carlo simulation to estimate risk with a 12‐month MSM deferral . That estimate used donor baseline data and input parameters based on the best available public health data, albeit very conservative.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, we considered the risk associated with only the window period, without taking into account any risk linked to testing and processing failures, as other studies have done . The false‐negative test rate was estimated at 0.05% in the United States and more recently at 0.04% in Great Britain .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we considered the risk associated with only the window period, without taking into account any risk linked to testing and processing failures, as other studies have done. [31][32][33] The false-negative test rate was estimated at 0.05% in the United States and more recently at 0.04% in Great Britain. 31,34 Applying a rate of 0.04% to that of confirmed HIV-positive donations between July 2016 and December 2017 (0.068 per 10,000 donations), the risk of an HIV-positive donation following a testing error was estimated at 0.0028 per 1 million donations, which is negligible.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous changes in blood policy in the US and internationally emanated from the federally-commissioned Institute of Medicine (IOM) Report. 6 Still other policies were developed in reaction to the hundreds of lawsuits in the US and the criminal proceedings in a number of countries including Canada and France. Canada reorganized its entire blood system as a consequence of the Royal Commission of Inquiry on the Blood System in Canada (Krever Commission).…”
Section: Public Policymentioning
confidence: 99%